2021
DOI: 10.3390/cancers13143395
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Functions and Clinical Significance of Circular RNAs in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is ranked as the second most commonly diagnosed disease in females and the third in males worldwide. Therefore, the finding of new more reliable biomarkers for early diagnosis, for prediction of metastasis, and resistance to conventional therapies is an important challenge in overcoming the disease. The current review presents circular RNAs (circRNAs) with their unique features as potential prognostic and diagnostic biomarkers in CRC. The review highlights the mechanism of action and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 252 publications
(331 reference statements)
0
5
0
Order By: Relevance
“… 43 ATP-dependent RNA helicase DDX42 protein is predicted to be an RBP and has shown experimental evidence in colorectal cancer progression. 44 Ro 60-kDa autoantigen is a known RBP that functions in non-coding RNA quality control while trafficking between the nucleus and cytoplasm. 45 To simply visualize the proteins that are significantly associated with NFIX, we took the top 200 significant (up- and down-regulated) proteins quantified from the circRNA-linear RNA comparison to build a network based on in silico analysis or experimental evidence in the STRING database ( Figure 5 E).…”
Section: Resultsmentioning
confidence: 99%
“… 43 ATP-dependent RNA helicase DDX42 protein is predicted to be an RBP and has shown experimental evidence in colorectal cancer progression. 44 Ro 60-kDa autoantigen is a known RBP that functions in non-coding RNA quality control while trafficking between the nucleus and cytoplasm. 45 To simply visualize the proteins that are significantly associated with NFIX, we took the top 200 significant (up- and down-regulated) proteins quantified from the circRNA-linear RNA comparison to build a network based on in silico analysis or experimental evidence in the STRING database ( Figure 5 E).…”
Section: Resultsmentioning
confidence: 99%
“…Predictive biomarkers are frequently used to identify high-risk patients and predict drug responses. Until now, several potential prognostic biomarkers have been discovered [27][28][29], but there were still no suitable molecular biomarkers applied in the clinic. The findings of our study suggested that FOCAD and its ubiquitination might be used to predict the outcomes of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years great hopes have been placed on lncRNAs and, especially, on circRNAs because of their association with clinicopathological characteristics of cancer patients and their stability in circulation. Similar to the other types of ncRNAs, circRNAs can act as oncogenes or tumor suppressor genes and are associated with cancer phenotypes [29,39].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, circIPO11 is being examined in liver cancer [16], circFUT8-in liver and bladder cancer [16,17], circABCB10-in breast, lung and non-small cell lung cancer [18][19][20] and circSMARcA5-in cervical, prostate, hepatocellular, and non-small cell lung cancer, as well as in glioblastoma multiforme [21][22][23][24][25][26][27]. With the exception of circABCB10 none of the above has been previously evaluated in CRC [28,29]. In our study we measured their baseline expression in the circulation of patients with stage III and stage IV CRC before the start of their treatment and in comparison to healthy controls.…”
Section: Introductionmentioning
confidence: 99%